(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
From a historical perspective, Lebanon’s social context has long been conducive to the emergence and development of Sunni jihadism, but the movement was too weak to challenge the status quo. However, the Syrian Civil War has changed the balance of power, putting Hezbollah on the defensive and weakening the Future Movement´s Sunni leadership. This has allowed the Lebanese jihadists to cooperate with the Islamic State and Jabhat al-Nusra, who see the Lebanese crisis as an extension of the Syrian war. As a result, they are playing an increasingly prominent role in the neighbouring country in a bid to spread violence and overstretch the military capabilities of the Lebanese army and Hezbollah.